An Unusual Method of Handling Marriage Nullity Cases: Canon 1608 (Roman replies and CLSA advisory opinions 1996, 1996)
This particular situation involved pronouncing five petitioners free to marry, without the benefit of a ''formal trial'' for any of them. In his letter to the Canon Law Society of America, Archbishop Grocholewski notes that [regarding these cases] "this Supreme Tribunal issued a decree concerning an unusual manner of handling cases of the nullity of marriage by a particular ecclesiastical tribunal.” The justification for this decision, according to the judicial vicar, were canons 1608, §4; 1150, and 1060. The Signatura's response to this approach is seen in the following letter/decree, first in Latin, and then in an English text edited by the Apostolic Signatura for publication.